Aplikasi Prakiraan Perkembangan Covid-19 Di Indonesia Menggunakan Metode Single Exponential Smoothing Berbasis Web - Tsinmi Tri Azkiya Waslin; Oris Krianto Sulaiman; Tasliyah Haramaini (STMIK Budi Darma, 2022)
ARSCoV2 (Severe Acute Respiratory Syndrome Coronavirus 2) is a virus cause of COVID-19 that has spread to many other countries. A variety of efforts is carried out mostly countries in the world to face this disease. The result of increased case of COVID-19 the economy is inspiring and providing pressure on the future economic growth including Indonesia’s economic growth. UN-defined COVID-19 pandemi, impact on sector transportation, tourism, trading, health and others. The purpose of this research is to design and create COVID-19 case development forecast in Indonesia by implementing REST API services and using the single exponential smoothing method as a mathematical method to calculate the development forecast COVID-19 cases in Indonesia are confirmed with the date to help minimize losses materials and immaterials, for the readiness of the Indonesian government in conducting rapid precautions and appropriately to help the general public to obtain COVID-19 and forecast information the development. Research results on COVID-19 data in Indonesia in March 2020 until April 2022 obtaining the value of the MAPE error model of 7.97% where 7.97% ≤ 10% so included in the level category high accuracy with forecast results in the next month, May 2022 is 5,327,773 cases.